Endophthalmitis outbreak caused by Fusarium oxysporum after cataract surgery - Rei Arasaki (American Journal of Ophthalmology Case Reports, 2022)
Purpose: To evaluate an outbreak of endophthalmitis caused by Fusarium oxysporum after cataract surgery. Methods: In the present study, we conducted a retrospective review of the medical records of cases of endophthalmitis that developed after cataract surgery. All eyes underwent phacoemulsification and intraocular lens implantation (PEA + IOL) at a single eye clinic on the same date. Symptoms of endophthalmitis occurred 21.5 ± 3.4 days after the cataract surgery. Results: Nine eyes of 9 patients with fungal endophthalmitis (5 males and 4 females) were enrolled in the current study. The mean age of the patients was 63.4 ± 8.5 years. Soon after the diagnosis of endophthalmitis, pars plana vitrectomy (PPV) had been performed in all the eyes. However, because there was no response to the first PPV plus antibacterial drug therapy, we performed repeat PPV for all the eyes, combined with IOL removal and antifungal therapy (natamycin eye drops plus oral voriconazole or fosfluconazole). After the antifungal drug therapy, no recurrence of endophthalmitis was observed in any of the operated eyes, and good visual outcomes were obtained. Fusarium oxysporum was identified by culture and sequencing analysis. Conclusion: Early diagnosis and appropriate, adequate treatment are needed for successful management of fungal endophthalmitis.